THE EFFECT OF SMART SPECIALIZATION ON THE EDUCATION SYSTEM IN BULGARIA - P. Atanasova (Trakia Journal of Sciences)
Smart specialization is not an imposed strategy, but a necessary adaptation of national and regional policies in modern times. It is the conditions of constantly decreasing resources and the adaptation of local economies to a new world order that requires an analysis of the education system, which should lead to justified change. The research period is 2014 - 2020 and the base year is 2014, the beginning of the measures in the direction of development of the Smart Specialization of the Regions in Bulgaria. Analyzed economic indicators are population, level of education, number of schools in the education system, and employment by economic activities. The study covers two levels - national and regional, to specify the need for followup. Performed economic analyzes demonstrate the specialization of the regions in the field of education. The conclusions that follow from the present study show the effect of smart specialization on the education system in the country, as well as the direction for future changes in educational structures.